Artificial Intelligence dalam Pasar Modal Syariah: Studi Bibliometrik terhadap Struktur Intelektual, Tren Riset, dan Future Research Agenda: Artificial Intelligence in Islamic Capital Markets: A Bibliometric Analysis of Intellectual Structure, Research Trends, and Future Research Agenda - Azwar Azwar; Abur Hamdi Usman; Muh. Ali Akbar; Andi Ahmad Mappangaja (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study maps the intellectual structure, research trends, and future research agenda of AI in Islamic Capital Markets using a bibliometric approach. With a descriptive-quantitative design and data from reputable international databases, it analyzes publication growth, key contributors (authors, journals, institutions, and countries), collaboration networks, thematic clusters, and thematic evolution. Results show a sharp increase in publications, especially since 2021, reflecting the rapid expansion of AI applications in Islamic capital markets amid global financial digitalization. Authorship and citation analysis identify Irfan M. as the most productive author, while Abakah et al. (2023) is the most influential work. However, collaboration network analysis reveals a fragmented structure, with zero betweenness centrality among authors, indicating weak interconnectivity between research clusters. At the journal level, the International Journal of Islamic and Middle Eastern Finance and Management and the Journal of Islamic Marketing dominate as key outlets. Institutionally, Federal Polytechnic Ilaro and Hamad Bin Khalifa University are leading contributors, while Indonesia emerges as the most productive country. Thematic analysis identifies four core pillars: (1) AI integration in Islamic finance, (2) investment and financial markets, (3) machine learning-based risk management, and (4) enabling technologies such as blockchain and big data. Thematic evolution indicates a shift toward integrated, value-driven research aligned with maqāṣid al-syarī‘ah, sustainability, regulatory governance, and AI-based investment optimization.